Carbapenem Resistance Profile of Acinetobacter baumannii Complex Strains in the Intensive Care Unit of a University Hospital in Northern Cyprus: 3-Year Follow-up - Meryem Güvenir; Emrah Güler; Kaya Süer (Galenos Yayinevi, 2021)
Objective:This study aimed to investigate the distribution of three-year carbapenem resistance of Acinetobacter baumannii complex (ABC) in hospital infections isolated from the intensive care unit in the last three years.Materials and Methods:The patients who had ABC infection in the Intensive Care Unit of Near East University Hospital between 2016-2018 were included in this study. The data of the patients were investigated retrospectively from the digital records and the Infection Control Committee data. The initial infection report of the patients who had multiple ABC infections was included in the study. SPSS Statistics 23.0 program was used for statistical analysis.Results:A total of 92 patients were diagnosed with ABC infection during the study period, including 22 (23.9%) in 2016, 31 (33.7%) in 2017 and 39 (42.4%) in 2018. Fifty-six patients (60.9%) were male and 36 (39.1%) were female. The mean age of the patients was 61.61±17.43 years (range, 22-89 years). The most common isolates were from tracheal aspirate (28.3%, 26 patients), sputum 27.2%, 25 patients) and urine samples (23.9%, 22 patients). Carbapenem-resistant ABC infection was detected in 65 patients (70.7%) and carbapenemsensitive ABC infection was found in 27 patients (29.3%). There was a statistically significant increase in carbapenem-resistant ABC strains over the years (p<0.05, p=0.012). Thirty-one of the 38 carbapenem-resistant patients were dead.Conclusion:ABC strains that cause high mortality infections can develop resistance to many antibiotic groups very quickly. Therefore, fatality due to multiple antibiotic-resistant ABC strains is increasing all over the world. It was seen that ABC infections had increased in our hospital over years. In parallel, there was a statistically significant increase in carbapenem-resistant ABC strains. Nowadays, it is essential to ensure proper application of isolation rules, to provide relevant personnel training and to prevent ABC infections with rational antibiotic use.